Android software-based tinnitus retraining therapy: efficacy in treatment of refractory tinnitus - Athavale, Aakriti Sanjay; Sahu, Pankaj Kumar; Singh, Roohie; Natraj, Rashmi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Tinnitus is described as a perception of sound in the absence of a sound stimulus. Despite the availability of a number of management strategies, the cure for tinnitus remains elusive. Tinnitus retraining therapy (TRT) combines sound therapy with directive counselling to address subjective tinnitus. This study was done to assess the efficacy of TRT in management of subjective tinnitus that is refractory to various tinnitus treatment strategies. The objectives of this study were to assess the efficacy of Android software TRT in management of refractory tinnitus and to observe the association of hearing status on response to TRT. Methods: Observational, analytical cohort study of 51 patients undergoing smartphone-based TRT. The assessment tools included comprehensive audiometric evaluation, two self -administered questionnaires tinnitus handicap inventory (THI) and tinnitus functional index (TFI) which were assessed at baseline (0), 6 weeks and at 12 weeks of TRT. Results: Statistical data analysis revealed significant improvement in perceived severity of tinnitus following TRT, reflected by improvement of THI and TFI scores (statistically significant, p<0.05). Mean pure tone average threshold was 22.1Hz. Additionally, no significant association was found between the hearing loss and the severity of tinnitus. Conclusions: There is significant improvement in self-perceived disability and severity following TRT as measured using THI and TFI. The results confirm the efficacy of TRT in management of patients with refractory tinnitus.